A Proposed Study of a Unified e-Portal for Citizens and Residents in the Sultanate of Oman - Ishaq Mubarak AL Hadhrami, Jayakumari (Journal of engineering sciences and information technology, 2018)
This study aims at suggesting a shared medium for all of the Omani government sectors. All governments increasingly use modern information technology (IT) to support their operation. In recent years, the main effort is investing into improving the quality and efficiency of service delivery, mainly through different e-government initiatives. E-Portal offers a wide variety of possibilities for delivering public services in new ways. One of the possible solutions, which has recently become a popular development trend of e-government officials, are E-portals, which not only join but also integrate services in the competence of different public institutions into one single window or entry point(Fan and Yang, 2015), accessible via the internet. The study is based on interviews and an online survey for data collection. The results show in figure #1 that there is an urgent need for a shared point to the services offered by the Omani government. This study promotes the foundation of integrated access to all the government institutions.